Influence of high-definition transcranial direct current stimulation to the parietal cortex on postural control: a single-blind randomized crossover study - Yang, Fan; Liu, Yang; Lv, Xianglin; He, Yaqi; Gao, Jinpeng; Zhang, Pei; Li, Qing; Peng, Zhongmei; Qian, Jinghua (Frontiers in Human Neuroscience, 2025)
BackgroundThe parietal lobe is an important cerebral cortex area for sensory information processing to maintain postural control. High-definition transcranial direct current stimulation (HD-tDCS) can improve the excitability of the target brain region. The purpose of this study was to investigate whether HD-tDCS applied to either unilateral or bilateral parietal lobes would improve postural control.MethodA single-blind randomized crossover experimental design was used. 18 healthy right-handed adults were recruited for unilateral and bilateral HD-tDCS, as well as sham stimulation. All participants completed the sensory organization test (SOT) and motor control test (MCT) under eyes open and eyes closed conditions before and immediately after each intervention. The equilibrium score (ES), composite score (CS), and sensory score (VIS, SOM, VEST, PREF) from SOT, along with latency and response strength from the MCT, were calculated. Two-way repeated measures analyses of variance (ANOVAs) were used for the dependent variables. Bonferroni’s post hoc tests were used in case of significant ANOVA results.ResultsThe composite latency increased significantly after right (p = 0.025) and bilateral (p = 0.004) stimulation under eyes open condition. When the balance plate moved large forward, the latency increased significantly after left (p = 0.003) and bilateral (p = 0.04) stimulation under eyes closed condition. For response strength, when the balance plate moved forward at different magnitude under eyes closed condition, they all decreased significantly after bilateral stimulation (p < 0.05).ConclusionThe parietal lobe participates in the modulation of automatic postural response. The primary function of the right parietal lobe in postural response is to process visual information, while the left is responsible for processing somatosensory information.